ADAPTING SUSTAINABLE LIVELIHOOD FRAMEWORK FOR HUMAN WELL-BEING ASSESSMENT IN BANTUL REGENCY - Kusumawardhani, Nadia Paramitha (Institut Teknologi Nasional Yogyakarta, 2019)
There is broad subject that ecosystem service influence human well-being (HWB), however HWB are unmeasurable variable, therefore it still not been integrated fully into ecosystem service assessment and spatial planning document in Indonesia. Provision of sustainable ecosystem services, especially food provisioning, is a challenge for Bantul Regency as it faces huge production deficits because of land conversion and urbanization, therefore, it will threaten the condition of its human well-being. It aims to determine the distribution of human well-being conditions as well as analyzing which capital is the basic capital for human development in Bantul Regency. This study evaluates and maps human well-being by using Sustainable Livelihood Framework (SLF), based on perspective of experts and stakeholders, then analyzed the spatial variation on landscape by mapping the area, and discussed how to achieve human well-being conditions by maximizing services from the ecosystem. Questioners were distributed to stakeholders that involved in development decision making in Bantul regency in Likert scale, then it was analyze to determine the scores of each indicator in every capital. Then regional boundary shapefile analysis in ArcMap was carried out to map the level of conditions of human well-being. Based on the analysis, Human Capital is the largest capital in the people’s welfare of Bantul, the highest condition is located in the Dlingo and Srandakan Districts. However, financial, physical and social capitals are located in the same area, which makes the Banguntapan, Sewon and Bantul Districts have the best human well-being conditions in all of Bantul Regency. This study also found that besides geographical conditions play an important role in producing different types of ecosystem services, social-economic factors is the most important factor in determining the difference in value of each capital in human well-being. Optimizing planning regulation has to consider these spatial patterns.